The Primary Gate of the Melaka Sultanate - Mustaffa, Fauzan; Baydoun, Ziad; Abidin, Mohamad Izani Zainal; Othman, Muhammed Fauzi; Din, Shamzani Affendy Mohd (International Journal of Membrane Science and Technology, 2023)
Based on the historical Malay, China and Arab textual account, there was a primary gate that marked the entrance to the royal compound of Melaka Sultanate before 1511. The primary gate was arguably among the most iconic construct and strategic to the Sultanate city, at security, socio-cultural, symbolic and aesthetic levels. However, no critical study has been conducted in tracing the form, position, and its relation to the municipality of the Sultanate Melaka City. This study employs narrative analysis framework to carefully investigate descriptive clues to provide the big picture on the primary gate of Melaka Sultanate in view of historical texts from Malay, China, and Arab; all of which were written within or close to the Sultanate period. The findings of the narrative analysis were compared to a collection of municipal plans from the Portuguese and Dutch Melaka eras. This reconstruction study also took precedence of an ancient Malay sultanate gate for the design process which can be seen carrying the tradition of Sultanate Melaka gate. The finding of the study suggests the form, position and orientation of the sultanate Melaka gate. The study also discusses and proposes the route which could possibly accommodate another 6 gates before reaching the sultanate Melaka palace. The study has limitations since it relies on English translation in dealing with ancient Portuguese texts. The long-term goal of this reconstruction study is to promote historical Melaka identity tourism, which is in line with SDGs 8.9 and 11.4.